Pengaruh Tangible, Reliability, Responsiveness, Assurance, Dan Empathy Terhadap Kepuasan Masyarakat Pengguna Layanan Paten Masa New Normal Di Kecamatan Sako - Trecy Austin (Jurnal Pemerintahan dan Politik, 2021)
The results of observations made by researchers in the field of the PATEN process in Sako District during the new normal period, the community was not yet disciplined in dealing with it online. Based on a survey, respondents were still regulated directly, because physical files still had to be collected at the PATEN counter for processing. The absence of access to online services does not hamper services, because there are fewer people who take care of files during the new normal period than before the Covid 19 pandemic. Sematang form) since 23 April 2020. The purpose of this study is to analyze the effect of service quality (tangibles, reliability, responsiveness, assurance, and empathy) on community satisfaction in Sako District and explain the dimensions of service quality (tangibles, reliability, responsiveness, assurance, and empathy). This type of research uses quantitative methods. Observations, questionnaires, interviews, and literature are used in data techniques. The method used in studying the data is Proportionate Random Sampling. The data quality test consisted of testing the validity and reliability of the data using multiple linear regression. The results showed that the t value was 1.985 with a significant value of 0.015 <0.05, so the results of the first problem formulation were Tangible, Assurance, and Empathy which had a significant effect on the variable of community satisfaction. The second problem formulation explains that the variable empathy is the variable that has the most dominant influence on the dependent or dependent variable (y) with the largest Beta value of 0.551. Keywords: Public Services, Community Satisfaction, Integrated District Administration Services